Serological Approaches for Trypanosoma cruzi Strain Typing. Issue 3 (March 2021) - Balouz, Virginia; Bracco, Leonel; Ricci, Alejandro D.; Romer, Guadalupe; Agüero, Fernán; Buscaglia, Carlos A.
Abstract : Trypanosoma cruzi, the protozoan agent of Chagas' disease, displays a complex population structure made up of multiple strains showing a diverse ecoepidemiological distribution. Parasite genetic variability may be associated with disease outcome, hence stressing the need to develop methods for T. cruzi typing in vivo . Serological typing methods that exploit the presence of host antibodies raised against polymorphic parasite antigens emerge as an appealing approach to address this issue. These techniques are robust, simple, cost-effective, and are not curtailed by methodological/biological limitations intrinsic to available genotyping methods. Here, we critically assess the progress towards T. cruzi serotyping and discuss the opportunity provided by high-throughput immunomics to improve this field. Highlights: Trypanosoma cruzi, the vector-borne protozoan agent of Chagas' disease, displays a complex population structure made up of multiple strains showing diverse genotypic and ecoepidemiological features. Typing of the infecting strain(s) directly in biological samples may shed new light on T. cruzi zoonotic distribution and, more importantly, may facilitate the study of possible associations between parasite genotype and Chagas' disease clinical outcome. Detailed descriptions of strain-specific antibody profiles or signatures emerge as an appealing approach for in vivo T. cruzi strain typing. High-throughput immunomics provides a unique opportunity to link the increasing ability to catalog variation among T. cruzi genomes to the identification of novel polymorphic targets of strain-specific B cell immunity.